Effectiveness of Yoga and Naturopathy in Managing IgE-Mediated Dermatitis: A Case Report - R, Subbiah; S, Ragul Prince; S, Prashanth (Indian Journal of Integrative Medicine, 2025)
IgE dermatitis is a chronic inflammatory skin disease associated with increased serum IgE levels and sensitization to a number of stimulant such as inhalants, food, and microbial allergens. An 18-year-old male patient, came with a complaint of severe itching and redness along with pain and swelling, then he was followed up in the outpatient department on inspection, we noted small papule-like lesions that have been oozing, especially seen over the neck region and on the elbows of the hands, for the past 5 months. His Serum IgE level was 350 IU/mL. He was diagnosed with a case of IgE-mediated dermatitis. He underwent Yoga and Naturopathy treatments for 5 months. Based on the parameters observed, serum IgE, EASI (Eczema Area and Severity Index), SCORAD (Scoring atopic dermatitis), and VAS (visual analogue scale) post-intervention showed improved changes, which indicates positive improvements in the condition. This result has proven the efficacy of Yoga and Naturopathic interventions in treating IgE-mediated dermatitis, helping to reduce the severity of symptoms and improves quality of life by quickening healing.